Linguistic Risk-Taking in Elementary School: Exploring the Children's Perspective through Semi-Structured Interviews (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2026)
This paper examines the communicative challenges (linguistic risks) that young learners (YL) encounter in daily life and the English as a foreign language (EFL) classroom, where their second language (L2) skills are developed. A literature review identified potential linguistic risks in the English classroom and supportive factors. Semi-structured interviews with five 4th graders were conducted and analyzed using qualitative content analysis to determine students’ perceived linguistic risks in school and everyday life, and what may help them manage these risks. The results suggest that YL associate linguistic risks with English class (speaking, comprehension) and that various factors may support students (peer group, teacher, learning strategies). These factors, as well as the risks themselves, are influenced by the context, including the interlocutors, the situation, and the physical location. Data analysis led to preliminary hypotheses for Linguistic Risk-Taking with YL in early English language teaching.
Keywords: Linguistic Risk-Taking (LRT); Elementary School; Early English Language Teaching (ELT); English as a Foreign Language (EFL); Young Language Learners